Sebuah Pendekatan TaRL terintegrasi Social Emotional Learning (SEL) dengan model PBL untuk meningkatkan minat dan hasil belajar siswa: - - Fajri, Nur Lailatul; Nurita, Tutut; Muslimah, Mar’atul (UNIB Press, 2024)
This research was motivated by students low interest and learning outcomes in science learning. The science learning process cannot fully meet students' needs and interests, causing low student learning outcomes. Teaching using the Teaching at The Right Level (TaRL) approach integrated with Social Emotional Learning (SEL) with the Problem Based Learning (PBL) model can facilitate various student learning characteristics and interests. The research aimed to determine the increase in learning interest and learning outcomes in science lessons on Elements, Compounds and Mixtures. This research used Classroom Action Research which was carried out in two cycles with each cycle containing four stages, namely planning, implementation, observation, then ending with reflection. Learning interest data was obtained through a learning interest questionnaire, while learning outcome data was obtained from written tests which were then analyzed quantitatively and qualitatively. The results showed that the average percentage of students' interest in learning before the action was 73.85% (fair) then increased to 79.97% (very high) after the action was given. In learning outcomes, an increase was obtained with an average score of 71.87 with learning completeness of 77.42% in cycle I and 82.19 in cycle II with learning completeness of 90.32%. Therefore, the SEL integrated TaRL approach with the PBL model can increase student interest and learning outcomes.